Instructions for Authors. - Krifka, Manfred (Linguistics & Philosophy, 2003)
Focuses on instructions for authors who plan to submit manuscripts to be published in the "Linguistics and Philosophy" journal. Aim and Objective of the publication; Request for submission of manuscripts and figures in electronic form in addition to the hard copy; Procedures on the review and presentation of the manuscript.